2013
DOI: 10.4103/1118-8561.125553
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its risk factors among bank employees of Sullia Taluk, Karnataka

Abstract: A B S T R A C TBackground: Hypertension is a leading cause of mortality in the world and is ranked third as a cause of disability-adjusted life years. Epidemiological studies have shown that sedentary life-style and stress are important risk factors for hypertension. The job of bank employees is both sedentary and stressful. Studies on hypertension among bank employees are sparse in India; hence, this study was undertaken to estimate the prevalence of hypertension and identify its risk factors in bank employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
30
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 12 publications
8
30
4
Order By: Relevance
“…The similar findings were revealed by other studies conducted in the bank employees. 15,19,20,24,25 Significant association has been found between years of experience and hypertension in a present study and a study by Prashanth et al 16 This may be due the fact that age also increases with years of experience.…”
Section: Table 4: Prevalence Of Hypertension In Bank Employees From Vsupporting
confidence: 49%
See 4 more Smart Citations
“…The similar findings were revealed by other studies conducted in the bank employees. 15,19,20,24,25 Significant association has been found between years of experience and hypertension in a present study and a study by Prashanth et al 16 This may be due the fact that age also increases with years of experience.…”
Section: Table 4: Prevalence Of Hypertension In Bank Employees From Vsupporting
confidence: 49%
“…Dietary factors: Similar to current study, the factors like type of diet, eating foods with high salt content, not eating fruits and vegetables daily were not found significantly associated with the hypertension in a study by Ganesh Kumar et al 20 Addition of extra salt while eating food was found significantly associated with hypertension in the study by Ganesh kumar et al and Mohmedirfan et al which is in contrary to the findings in this study and a study by Ismail et al 15,19,20 Mixed diet was found significantly associated with the hypertension in a study by M.H. et al whereas it was not found significantly associated with hypertension in a study by Ismail et al 24,15 Just like Physical activity, dietary changes are also important part of -Non-pharmacological treatment‖ of hypertension.…”
supporting
confidence: 46%
See 3 more Smart Citations